A Proposed Procedure for Rapid Development of Inbred Lines for the Production of Hybrid Maize in Nigeria - FAKOREDE, M. A. B. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A procedure is described for the rapid development of inbred lines to be used as parents of high-yielding hybrid cultivars of maize (Zea mays). This procedure involves the production of S1 lines from three unrelated populations A, B, C whose Fl hybrids are known a priori to demonstrate significant yield heterosis. The Sl lines are evaluated per se and S2 lines obtained from the performing 5 or more Sl lines from a population are intercrossed with those from the other populations to give 75 or more S2 x S2 crosses. The S2 x S2 crosses are evaluated with check cultivars (e.g. cultivar hybrids, the best widely grown cultivars and single-cross hybrids, if available) and the top 5 are selected for the National Zonal Maize Yield Trials (NZMYT) coordinated by the National Cereals Research Institute (NCRI), Ibadan. S4 x S4 hybrids of these top 5 selections are evaluated in the NZMYT as well as several other locations available to the researcher and inbred lines of the best 1 or 2 hybrids are released as parent materials. The advantages of this procedure include (i) simultaneous inbreeding and evaluation trials, (ii) flexibility for concurrent population improvement and extraction of inbredlines, and (iii) with two rainfed cropping seasons and an off-season with irrigation facilities, near-homozygous inbred lines (F 0.99) can be obtained within 3 calendar years.